The Effect of Liquidity, Profitability and Leverage on Company Value with Dividends as a Moderation Variable in a Company Included in the LQ45 Index on the Indonesia Stock Exchange Year 2016-2019 - Indika Candra Putra; Sri Hermuningsih; Gendro Wiyono (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2021)
This study discusses liquidity, profitability and leverage on firm value with dividend policy as a moderating variable. The sampling technique uses purposive sampling method to determine the sample based on the consideration of researchers. Data analysis uses Partial Least Square (PLS), which is a SEM-based variant, with SmartPLS software. The results showed that: 1) liquidity did not have a significant positive effect on firm value, 2) Profitability did not have a significant positive effect on company value, 3) leverage had no significant positive effect on firm value, 4) dividend policy was unable to significantly moderate the effect of liquidity on company company value, 5) dividend policy is not able to moderate the effect of profitability on significant corporate value, 6) dividend policy is not able to moderate the effect of leverage on company value significantly.